The Role of Adjuvant Chemotherapy in Metaplastic Breast Carcinoma: A Competing Risk Analysis of the SEER Database - Lan, Tian; Lu, Yunyan; Zheng, Ruzhen; Shao, Xiying; Luo, Hua; He, Junling; Yang, Huifen; Xu, Haibin; Wang, Xiaojia; Hu, Zujian (Frontiers in Oncology, 2021)
Purpose: Chemotherapy is the clinically recommended treatment for patients with operable metaplastic breast carcinoma (MBC); however, its impact remains controversial. This study investigated the possible role of chemotherapy in the treatment of MBC. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was used to identify the operable MBC patients. The competing risk analysis along with the propensity score matching (PSM) method was performed to evaluate the effect of chemotherapy. Moreover, a competing risk nomogram was built to identify prognosis in patients with MBC. Results: Of the 1137 patients with MBC, 775 received chemotherapy, and 362 did not receive chemotherapy. The 5-year cumulative incidence of breast cancer-specific death (BCSD) showed similar outcomes in both the Chemo and No-Chemo groups (21.1% vs. 24.3%, p=0.57). Chemotherapy showed no apparent association with BCSD (HR, 1.07; 95%CI, 0.72-1.60; p=0.72), even after subgroup analysis or PSM. Race, tumor size, lymph node status, and radiation were identified as the significant factors for MBC after a penalized variable selection process. Besides, a competing risk nomogram showed relatively good accuracy of prediction with a C-index of 0.766 (95%CI, 0.700-0.824). Conclusion: Our findings demonstrated chemotherapy did not improve BCSD for operable MBC patients. Thus, it may indicate the need to reduce exposure to the current chemotherapy strategies for patients with resectable MBC. Additionally, some novel treatment strategies are required urgently to identify and target the potential biomarkers.